1996
DOI: 10.1055/s-2007-972835
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Validity of Magnetic Resonance Imaging in Acute Knee Injuries With Hemarthrosis: A Single-Blinded Evaluation in 69 Patients Using High-Field MRI Before Arthroscopy

Abstract: Sixty-nine patients with traumatic knee hemarthrosis were evaluated an average of 3 days after trauma by high field (1.5T) magnetic resonance imaging (MRI) using sagittal T1, T2-weighted and coronal 3D-gradient echo images. All knees were arthroscopically examined shortly afterwards. The diagnostic validity of MRI for intraarticular pathology was determined using arthroscopy as golden standard. All patients had pathological findings on arthroscopy. The injuries were sports-related in 77% of the cases. MRI was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
35
1
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 3 publications
4
35
1
5
Order By: Relevance
“…Jee et al concluded that MRI in the presence of ACL tears has lower sensitivity for detecting meniscal tears due to missed lateral meniscal tear [7]. Lundberg et al found sensitivity and specificity of 74% and 66%, respectively, for medial and 50% and 84% for lateral meniscus [10]. They found that MRI could not replace arthroscopy in diagnosis of acute knee injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Jee et al concluded that MRI in the presence of ACL tears has lower sensitivity for detecting meniscal tears due to missed lateral meniscal tear [7]. Lundberg et al found sensitivity and specificity of 74% and 66%, respectively, for medial and 50% and 84% for lateral meniscus [10]. They found that MRI could not replace arthroscopy in diagnosis of acute knee injuries.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Only a few studies were reported, and they were not comparative studies. Regarding the diagnostic validity of MRI in acute knee injuries, Lundberg et al 24 suggested that the low diagnostic accuracy of MRI for intra-articular pathologic conditions with hemarthrosis may be attributed to catabolic processes in meniscal and chondral tissues during the hemoglobin degradation process.…”
mentioning
confidence: 99%
“…Our results show that the sensitivity and specificity of MRI for diagnosing meniscus lesions (76%) [2,16,17]. A high NPV means that a negative MRI is reliable and this would justify an expecting approach instead of subacute surgery.…”
Section: Discussionmentioning
confidence: 78%
“…It is known to have high sensitivity and specificity for ACL-tears and lesions of the medial meniscus [2,10,11], although there are also false-positive results [12,13].…”
Section: Introductionmentioning
confidence: 99%